Dust impact and attitude analysis for JAXA’s probe on the Comet Interceptor mission - Machuca, P.; Ozaki, N.; Sa´nchez, J. P.; Felicetti, Leonard (Elsevier, 2022)
Comet Interceptor (Comet-I), to be launched in 2029 as a piggyback to ESA’s ARIEL mission, is aimed to perform the first fly-by of a pristine long-period comet. The mission will be composed of a main spacecraft, SC A (ESA), and two small probes to be released prior to the fly-by, SC B1 (JAXA) and SC B2 (ESA). This work analyzes the attitude performance of JAXA’s 24U-sized spacecraft through the dust environment of a yet-to-be-discovered target comet. Main challenges to the mission are associated to the high levels of uncertainty and extremity of fly-by conditions: highly-active dust environment, uncertain fly-by altitude (750 ± 250 km (1σ), as of 2021), and large and unknown relative fly-by speeds (15–70 km/s). A Monte Carlo analysis is performed to characterize the effect of dust particle impacts on the attitude of SC B1, and to evaluate the likelihood of satisfying pointing and angular velocity requirements of the science camera. Analysis initially shows that particles of mass 10−8–10−5 kg represent the most relevant source of perturbation due to their transferred angular momentum and likelihood of being encountered, and saturation of reaction wheels is shown unlikely given the large fly-by speeds and short fly-by durations (20 min–2 h). More detailed analysis ultimately suggests a probability larger than 90% of satisfying science camera requirements despite the extreme, uncertain fly-by conditions, dust environment, and component inaccuracies (star tracker, gyroscopes, and reaction wheels). Results also show that upgrading the reaction wheel that is implemented along the camera line-of-sight can improve, but only marginally, attitude performance, and proper alignment of solar arrays parallel to the incoming flow of particles is shown essential to maximize probability of success.
Keywords: Long-period comet; System requirements; Monte Carlo analysis